Uporządkuj jednomiany
a) y*6x =
b) -5b*7ba*(-2) =
c) x*(-6)x*y =
d) 2x*3x(do kwadratu ) =
e) 12cd*0,2c(do kwadratu) * d( do sześcianu )
f) (-x)*(-a)*12a*(0,3x(do kwadratu ) =

Przedstaw w jak najprostszej postaci
a) 16x-5y-6-21x+19y-8 =
b) -(9a-b+7) + ( 6+a-8b ) =
c) 5(x-3y) - 4(x-2)+(y-1) =
d) 2x(4,1 xy - 0,5y +3,2x) - (5x(do kwadratu) - 3,4xy + 1,2x (do kwadratu) y) * 3
e) (3x-5) - (2x + 4)=
f) 4(3x - 5) - 3(2x+4)=
g) (7x-3) -4 (2x+4)+7x
h) 5(a-b)-7a (a-b)

3

Odpowiedzi

2010-03-26T08:10:21+01:00
1
ą)6xy
b)70ab²
c)-6x²y
d)6x³
e)2,4c³d³
f)3,6a²x²
2
a)-5x+14y-14
b)-9a+b-7+6+a+8b=-8a+9b-1
c)5x-15y-4x+8+y-1=x-14y+7
1 4 1
2010-03-26T08:17:55+01:00
A) y*6x =6xy
b) -5b*7ba*(-2) =70ab²
c) x*(-6)x*y =-6x²y
d) 2x*3x² =6x³
e) 12cd*0,2c²* d³=2,4c³d³
f) (-x)*(-a)*12a*(0,3x² =3,6a²x²




2010-03-26T09:11:08+01:00
Uporządkuj jednomiany
a) y*6x = 6xy
b) -5b*7ba*(-2) = 70ab²
c) x*(-6)x*y = -6x²y
d) 2x*3x(do kwadratu ) = 6x³
e) 12cd*0,2c(do kwadratu) * d( do sześcianu ) = 2,4c³d³
f) (-x)*(-a)*12a*(0,3x(do kwadratu ) = 3,6a²x²

Przedstaw w jak najprostszej postaci
a) 16x-5y-6-21x+19y-8 = -5x+14y-14
b) -(9a-b+7) + ( 6+a-8b ) = -9a+b-7+6+a+8b=-8a+9b-1
c) 5(x-3y) - 4(x-2)+(y-1) = 5x-15y-4x+8+y-1=x-14y+7
e) (3x-5) - (2x + 4)=3x - 5 - 2x -4 = x - 9
f) 4(3x - 5) - 3(2x+4)=12x - 20 - 6x -12 = 6x -32
g) (7x-3) -4 (2x+4)+7x = 7x - 3 - 8x -16 + 7x = 6x - 19
h) 5(a-b)-7a (a-b) = 5a - 5b - 7a² + 7ab